PENGARUH LEVERAGE, PROFITABILITAS, FIRM SIZE, DAN LIKUIDITAS TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI - Pradiana, Nindya; Yadnya, I Putu (E-Jurnal Manajemen; Vol 8 No 4 (2019)DO - 10.24843/EJMUNUD.2019.v08.i04.p13, 2019)
Stock return is an advantage obtained by investors in stock investment. One sector whose stock returns fluctuate and has a high inventory turnover is the consumer goods industry. The existence of stock return fluctuations is the background of this study which aims to determine the effect of leverage, profitability, firm size and liquidity on stock returns on the consumer goods industry sector companies in the Indonesia Stock Exchange in the 2014-2016 period. The sample used in this study amounted to 33 companies. The method of determining the sample used in this study was purposive sampling method. The data analysis technique used in this study is multiple linear analysis. The results of this study are leverage variables proxied by DER which have a positive and significant effect on stock returns. Profitability proxied by ROE has a positive and insignificant effect on stock returns. Firm size has a positive and significant effect on stock returns. Liquidity which is proxied by QR has a negative and insignificant effect on stock returns. Keywords: debt to equity ratio, return on equity, firm size, quick ratio, stock return